Research of the mechanism of spatholobi caulis for immune-inflammatory of osteoarthritis based on clinical data mining,network pharmacology and cell experiment verification - Mingyu He; Jian Liu; Yanyan Fang; Yanqiu Sun; Fanfan Wang; Xu Li; Qi Han (Elsevier, 2024)
Background: Traditional Chinese medicine is widely used in the treatment of osteoarthritis. This study explores the therapeutic effect of Traditional Chinese Medicine (TCM) on osteoarthritis (OA), as well as the mechanism by which Spatholobi Caulis (SPC) improves the immune-Inflammatory response of OA. Methods: The clinical data mining techniques to evaluate the efficacy of Caulis spatholobi in treating OA, and elucidated its mechanism of action using network pharmacology, molecular docking, and cell experiments. The random walk model was applied to systematically evaluate the therapeutic efficacy of Chinese herbal medicine on OA. Results: The evaluation based on the clinical data mining showed that TCM is effective in improving ESR, CRP, C3, C4, and PLT. Data mining results showed significant OA treatment. Network analysis results showed that it may fight OA by targeting JUN, ESR1 and PPARG; molecular docking results showed good JUN, ESR1, PPARG and active component formononetin. Finally, in vitro experiments conducted the preliminary validation of formononetin for the core target of FLS. Cell proliferation was measured by CCK-8, and JUN, ESR1, PPARG protein, and mRNA expression was measured by quantitative real-time RCR at 48 h after drug intervention. Conclusion: The present study demonstrated that the SPC effectively relieved immune inflammation indicators in OA patients. Formononetin, the main active component of the chicken blood vine, acts to reduce the immune validation response in OA patients by reducing the expression of ESR1, JUN, and PPARG.